Amplification of bacterial genomic DNA by the polymerase chain reaction and direct sequencing after asymmetric amplification: application to the study of periplasmic permeases. - Shyamala, V (1989)
The polymerase chain reaction (PCR) has been used to amplify DNA fragments by using eucaryotic genomic DNA as a template. We show that bacterial genomic DNA can be used as a template for PCR amplification. We demonstrate that DNA fragments at least as large as 4,400 base pairs can be amplified with fidelity and that the amplified DNA can be used as a substrate for most operations involving DNA. We discuss problems inherent in the direct sequencing of the amplified product, one of the important exploitations of this methodology. We have solved the problems by developing an "asymmetric amplification" method in which one of the oligonucleotide primers is used in limiting amounts, thus allowing the accumulation of single-stranded copies of only one of the DNA strands. As an illustration of the use of PCR in bacteria, we have amplified, sequenced, and subcloned several DNA fragments carrying mutations in genes of the histidine permease operon. These mutations are part of a preliminary approach to studying protein-protein interactions in transport, and their nature is discussed.